Evaluation of Doses to Target Volume and Organs at Risk by Conventional versus RTOG Contouring Based 3D Conformal Plans in Breast Cancer: A Prospective Study - Prabha Verma; Madhup Rastogi; Ajeet Kumar Gandhi; Rohini Khurana; Anoop Kumar Srivastava; Avinav Bharati; Rahat Hadi; Niraj Agarwal (Journal of Clinical and Diagnostic Research, 2022)
Introduction: In radiotherapy, conventional field borders have often little anatomical correlation with the draining lymphatics. So, with the availability of more conformal techniques and delineation guidelines, an evident need exists to optimise our treatment plans with more focus on planning and dosimetric aspects. Aim: To evaluate the differences in dosimetric parameters to the Organs at Risk (OARs) and target volumes in patients treated with conventional plans vis-à-vis Radiation Therapy Oncology Group contour-guided treatment plans. Materials and Methods: A prospective interventional study was conducted in which 30 patients of histopathologically proven Infiltrating Ductal Carcinoma (IDC) breast, with age range of 18 to 80 years were enrolled. Patients were treated with 50 Gray in 25 fractions of radiation with additional 10 Gray in 5 fractions boost in Breast Conserving Surgery (BCS) patients by conventional treatment plans. Radiation Therapy Oncology Group (RTOG) guidelines were used for breast/Chest Wall (CW), axillary nodes, Supraclavicular Fossa (SCF), and Internal Mammary Node (IMN) delineation. OARs included heart, Ipsilateral (I/L) lung, Contralateral (C/L) breast, oesophagus and spinal cord. Dose-Volume Histograms (DVHs) for these contours were generated from conventional treatment plans. Further, new treatment plans were generated to cover >90% of Planning Target Volume (PTV) by 90% isodose line. DVH parameters of these two plans were compared using paired t-test. A p-value of <0.05 was considered statistically significant. Results: Of the total 30 cases, the mean volume of breast/CW PTV covered by 90% isodose line (V90) was better in RTOG plan as compared to Conventional plan (93.39 vs 90.39, p-value=0.001). Similarly, mean V90 for total axilla (97.44 vs 90.39, p-value=0.0001) and combined PTV (92.60 vs 88.81, p-value=0.0001) was better with RTOG plan. For OARs, conventional vs RTOG plans; Dmean for heart was 2.56 vs 2.60 Gy, p-value=0.63), I/L lung V20Gy was 28.77 vs 28.94%, p-value=0.71) and V5Gy for C/L breast was 0.48 vs 0.54%, p-value=0.47), respectively. In cases where IMN was irradiated, mean doses to the heart, I/L lung V20Gy, and contralateral breast V5Gy increased significantly. Conclusion: The present study showed that RTOG target volumes had inadequate coverage in conventional plans. On the contrary, plans directed at RTOG contours provided statistically better coverage for target volumes without increase in the doses to the OARs. In patients with IMN irradiation, the doses to some OARs were increased in RTOG as compared to conventional plans.